Influence of soil depth on seedling growth and development of Amaranthus viridis L. after amendment with organic fertilizer - Beckley IKHAJIAGBE; Augustine W. OJANIKELE; Barka P. MSHELMBULA; Gloria O. OMOREGIE; Moteniola C. ADEBIYI (Studia Universitatis Babeș-Bolyai. Biologia, 2025)
The implications of applying organic fertilizers made from dried cow dung and food waste on the seedling development and growth of Amaranthus viridis at different soil horizons was examined in the current study. The experiment was set up in a completely randomized design, with 6 profile depths x 3 fertilizer treatments x 3 replicates each, totaling 54 bowls. The set up was left for 5 weeks. The findings demonstrated that cow dung manure provided adequate plant nutrients for enhancing seedling growth A. viridis. Although 0.05 g seeds of A. viridis was sown in the bowls, emergence capacities under varying soil conditions differed. Amending the soils with food waste manure hampered emergence capacities of the test plant. There were only six (06) sprouts at the first week compared to 46 in the control. Despite the observation that soil horizon and organic fertilizer application had no discernible effect on the root length of 5 - week - old seedlings (which varied between 1.3 cm and 2.3 cm), the use of manure was associated with a decrease in foliar chlorosis incidence. Without manure, foliar chlorotic incidence was 58 % in the 61 – 75 cm soil profile depth, compared to 35.0 – 35.2 % when soils were amended with either cow - dung or dried food waste manure. Ultimately, while deeper soil horizons initially posed challenges for growth, soil amendment successfully alleviated these unfavorable conditions.